Pediatric heart transplantation in India: Transplantation of an adult heart in a child - Sandeep Seth; Milind Hote; Sandeep Chauhan; Dinesh Chandra; Kalyani Ganeshan; Rajeev Maikhuri; Mukesh Kumar; Shyam S Kothari; Balram Airan (Journal of the Practice of Cardiovascular Sciences, 2015)
After the first successful adult heart transplant in India at All India Institute of Medical Sciences, in 1994, we did our first pediatric heart transplant in 2015. An adult heart was successfully transplanted into a 10-year-old child. The steps from planning to the execution of the surgery and successful discharge of the patient are hereby discussed.